IT Sector in Poland — Opportunity for Enterprise Development - Szajt, M. (Электронное моделирование, 2009)
The study contains the analysis of IT sector. The author describes the situation of this sector in Poland and other European countries by indicating development opportunities and potential barriers. In the research part a linear equation model, which indicates the relation between broadband access and total turnover, was applied.